Project sponsorship : achieving management commitment for project success - Englund, Randall L.; Bucero, Alfonso, 1956- (Project Management Institute, Inc., 2015)
The second edition of Project Sponsorship-which includes an Appendix with new case studies, expanded assessment tools, and templates-shows how project sponsors and project managers can develop the skills they need to manage successful projects. Randall L. Englund and Alfonso Bucero-experts in the field of project management-have written the definitive guide for educating all stakeholders on the nature of project sponsorship. They describe in detail the responsibilities of the project sponsor, from communications and liaison, selection and training, problem solving, mentoring, and feedback, to the review of project execution. The project sponsor and manager learn how to negotiate effectively with each other and the project team to achieve their commitments.